IMPROVING STUDENT LEARNING MOTIVATION THROUGH LEARNING ASSISTANCE ACTIVITIES - Uswatun Solikhah; Muhammad Sholikhun; Laili Syarifah (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2022)
A student very much needs student learning assistance at home; this is important considering the teachers' limitations in teaching students in the classroom. Tutoring is an effort to assist students in better understanding the material. If a student already understands, it will affect the enthusiasm and motivation to learn from now on to the future. This study aims to foster student learning motivation through the level of student understanding of a material implemented through tutoring activities. The method in this study used the PAR (Participation Action Research) method. Participatory Action Research (PAR) is a research method carried out in a participatory manner among community members, namely Santri at TPQ Nurudholam Dusun Sawangan. The results of the implementation of this tutoring program were able to foster students' enthusiasm for learning, which was proven enthusiastically during learning mentoring activities.